Haematological and haemorheological changes associated with cigarette smoking. Issue 9 (September 1985) - Galea, G; Davidson, R J
Abstract : A prospective study was undertaken to establish the haematological and haemorheological changes associated with long standing cigarette smoking in 20 heavy smokers and to assess whether any such changes were reversible after smoking was stopped. Highly significant differences were observed in whole blood viscosity, plasma viscosity, plasma fibrinogen concentrations, packed cell volume, and carboxyhaemoglobin concentrations between smokers and non-smokers. Ten of the subjects were followed up for two weeks after stopping smoking by which time whole blood viscosity and carboxyhaemoglobin concentrations had improved significantly and indications of improvement could be seen in all other measurements. Two of these subjects were further followed up for two months when all the measured variables were comparable with those in non-smokers. No correlation could be established between carboxyhaemoglobin concentration and any of the other variables. Although patients' compliance may be difficult to obtain, further prospective studies would be required to confirm our findings.